Расчетная оценка толщины слоя индукционных электрических зарядов в металлическом проводнике - Баранов, М.И. (Електротехніка і електромеханіка, 2011)
A formula is obtained for approximate calculation of the thickness of a layer of excess electric charges generated at the ends (butt ends) of a metallic conductor under action of electromagnetic induction.